Associations of age at menarche and age at menopause with diabetes among postmenopausal women in Chongqing, China. Issue 7 (25th May 2022) - Yuan, Yun; Bu, Xiaoqing; Xiao, Meng; Chen, Liling; Tang, Wenge; Yuan, Xinyu; Ding, Xianbin; Tang, Xiaojun
Abstract: Background: Existing studies on the association of age at menarche and age at natural menopause with diabetes are conflicting. Objective: To explore the associations of age at menarche and age at natural menopause with diabetes, and to estimate whether body mass index, abdominal obesity, hypertension, and dyslipidemia would influence the relationships. Methods: In this cross‐sectional study, 5090 postmenopausal women were included from the China Multi‐Ethnic Cohort Study (CMEC) baseline in Chongqing province. Questionnaires, physical examinations, and biological samples testing were conducted. Logistic regression was used to generate odds ratios (ORs) and 95% confidence intervals (CIs). And restricted cubic splines were performed to evaluate the pattern of association between ages at menarche and menopause with diabetes. Results: The adjusted ORs for diabetes grouped by age at menarche (<12, 12–17, >17 years) were 0.76 (95%CI: 0.42–1.40), 1.00 (reference), and 0.73 (95%CI: 0.57–0.94). Similarly, the adjusted ORs for diabetes grouped by age at menopause (<44, 44–52, >52 years) were 1.38 (95%CI: 1.04–1.82), 1.00 (reference), and 1.11 (95%CI: 0.89–1.39). No significant interaction of age at menarche and menopause with body mass index, abdominal obesity, hypertension, and dyslipidemia in odds of diabetes was observed. Conclusion: Late menarche is associated with a lower prevalence of diabetes, while early natural menopause is associated with a higher prevalence of diabetes. No significant effect modification was observed by body mass index, abdominal obesity, hypertension, or dyslipidemia.